Synthesis of ribosomal proteins during the cell cycle of the yeast Saccharomyces cerevisiae. - Elliott, S G (1979)
Centrifugal elutriation was used to separate yeast cells by their cell cycle position. The rate of synthesis of ribosomal proteins showed a constant exponential increase through the cell cycle.